1992
DOI: 10.1128/mcb.12.9.3776
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of protein kinase C zeta subspecies in maturation of Xenopus laevis oocytes.

Abstract: A number of studies have demonstrated the activation of phospholipase C-mediated hydrolysis of phosphatidylcholine (PC-PLC) both by growth factors and by the product of the ras oncogene, p21ras. Evidence has been presented indicating that the stimulation of this phospholipid degradative pathway is sufficient to activate mitogenesis in fibroblasts as well as that it is sufficient and necessary for induction of maturation in Xenopus laevis oocytes. However, the mechanism whereby PC-PLC transduces mitogenic signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 22 publications
8
109
1
Order By: Relevance
“…First, PKCB was required for Ras-induced maturation in Xenopus oocytes (Dominguez et al, 1992) and serum-stimulated mitogenic signaling in mammalian cells (Berra et al, 1993). Second, the regulatory NH 2 -terminal fragment of PKCB showed preferential binding to Ras-GTP in vitro and a peptide corresponding to Ras residues 17 ± 44 blocked this interaction.…”
Section: Ras Mediates Its Actions Through Interaction With Multiple Ementioning
confidence: 99%
“…First, PKCB was required for Ras-induced maturation in Xenopus oocytes (Dominguez et al, 1992) and serum-stimulated mitogenic signaling in mammalian cells (Berra et al, 1993). Second, the regulatory NH 2 -terminal fragment of PKCB showed preferential binding to Ras-GTP in vitro and a peptide corresponding to Ras residues 17 ± 44 blocked this interaction.…”
Section: Ras Mediates Its Actions Through Interaction With Multiple Ementioning
confidence: 99%
“…Cells overexpressing PKCqx did not show any further enhancement, indicating that the effect of insulin on cAMP accumulation was unique to the expression of PKC@ In contrast to the conventional PKC isoenzymes that are activated by Ca and diacylglycerol, PKC-~ is activated by arachidonic acid and phosphatidylinositol 3,4,5-triphosphate (PIP3) [9,10], which are products of insulin or other growth factor receptor stimulation [21,22]. Indeed, a recent study has shown that PKC-~ is involved in the physiological functions of insulin in vivo [11]. Stimulation of these receptors initiates a cascade of phosphorylation reaction within the cell, promoting cellular growth and differentiation [23].…”
Section: T-omentioning
confidence: 99%
“…These isoenzymes are difficult to study because of the lack of specific activators and inhibitors [7,8]. More recent studies have suggested that atypical isoenzymes are activated by extracellular stimuli such as insulin and other growth factors [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies raised against peptides specific for the different isoforms of PKC have been used as a powerful tool to examine the presence of the members of the PKC family in different cells and tissues. Among them, the presence of aPKCc has received a growing interest since this PKC isoform has been shown to be involved in mitogenesis in several systems [5,6]. C-Terminus-directed antipeptide antibodies have been widely used to study *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%